Pseudomonas prosekii sp. nov., a novel psychrotrophic bacterium from Antarctica - Kosina, Marcel; Barták, Miloš; Mašlaňová, Ivana; Pascutti, Andrea Vávrová; Sedo, Ondrej; Lexa, Matej; Sedláček, Ivo (Current microbiology, 2013)
During Czech expeditions at James Ross Island, Antarctica, in the years 2007-2009, the bacterial diversity of the genus Pseudomonas was studied. Twelve fluorescent Pseudomonas strains were isolated from various samples and were subjected to a detailed taxonomic study. A polyphasic approach included genotypic and phenotypic analyses. The genotypic analysis involved sequencing of rrs, rpoB and rpoD genes, DNA-DNA hybridization (DDH) studies as well as manual ribotyping using HindIII endonuclease. The phenotypic characterization included conventional tests as well as biotyping using the Biolog system, protein profiling by SDS-PAGE, and MALDI-TOF MS analysis. Our taxonomic study revealed that all isolates belonged to the same Pseudomonas species with psychrotrophic growth not exceeding 37 °C. The cultures showed a unique position among the phylogenetically related pseudomonads. DDH experiment between the proposed type strain of the antarctic isolates and the closest neighbour P. arsenicoxydans CCM 8423(T) showed only 40.9-50.1 % similarity, thus confirming that the characterized strains do not belong to the P. arsenicoxydans species. According to the results obtained we propose the name P. prosekii sp. nov. for this novel Pseudomonas taxon with type strain AN/28/1(T) (=CCM 7990(T) and LMG 26867(T)).
Keywords: Antarctic Regions; DNA bakterií; Antarktida; Ribotyping; DNA, Ribosomal; Phylogeny; DNA-Directed RNA Polymerases; sigma faktor; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; Sigma Factor; RNA ribozomální 16S; Cluster Analysis; ribotypizace; RNA, Ribosomal, 16S; mikrobiologie životního prostředí; sekvenční analýza DNA; DNA, Bacterial; Environmental Microbiology; fylogeneze; shluková analýza; ribozomální DNA; Bacterial Typing Techniques; Nucleic Acid Hybridization; hybridizace nukleových kyselin; techniky typizace bakterií; DNA řízené RNA-polymerasy; Pseudomonas